EVALUASI PELAKSANAAN DAN PELAPORAN LAPORAN PERTANGGUNGJAWABAN BENDAHARA PENGELUARAN PADA KANTOR KELURAHAN LAPANGAN KECAMATAN MAPANGET KOTA MANADO - Aloa, Clifford; Manossoh, Hendrik; Mawikere, Lidia (Universitas Sam Ratulangi, 2020)
The accountability report represents responsibility for the village office funds obtained. This study discusses the implementation and accountability report of treasurers published. The type of this study is qualitative approach with descriptive method as analytical method. This study finds that the Responsibility Report of the Mapanget Field Office in Manado City is accordance to Permendagri 55 of year 2008 and Permendagri 130 of year 2018.